Pembelajaran Tematik Terpadu dengan Pendekatan Saintifik di Sekolah Dasar - Reinita Reinita; Sri Wahyuni (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2020)
This research is aimed to describe the improvement of integrated thematic learning process by using scientific approach. This was a classroom action research which used qualitative and quantitative approaches which is done in 2 cycles. The subject in this research is the teacher and 33 students of 1st grade in SDN 04 Birugo Bukittinggi. The result shows that the improvement: a) lesson plan in the first cycle was 83,33%, second cycle was 91,67%, b) Implemetation in teacher aspect in the first cycle was 81,67%, second cycle was 95%, c) Implementation in student aspect in the first cycle was 81,67%, second cycle was 95%. So, Scientific approach improve study of Integrated Thematic in elementary school.